2013
DOI: 10.1063/1.4857095
|View full text |Cite
|
Sign up to set email alerts
|

Extremely efficient exciton fission and fusion and its dominant contribution to the photoluminescence yield in rubrene single crystals

Abstract: Measurements of photoluminescence yield over a wide range of excitation power in rubrene single crystals reveal a transition between a low-yield region and a region with a yield more than an order of magnitude larger. This transition occurs at an excitation density of 3 × 1020 cm−3 absorbed photons per second. This power dependence is predicted in case of an extremely efficient conversion between singlet and triplet excitons through fission and fusion. Triplet fusion starts contributing to rubrene's photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 17 publications
5
53
0
Order By: Relevance
“…This was consistent with some previous reports that non-geminate triplets did not play an important role in the fission/fusion dynamics in amorphous organic solids [16,19]. This differs considerably from previous observation of triplet dynamics in rubrene crystals [24][25][26], where triplet excitons can freely diffuse in crystal and collide with each other to form intermediate 1 (TT) i states. In that case, the intensity of delayed fluorescence is proportional to n(t) 2 , where n(t) is triplet exciton density.…”
Section: Resultssupporting
confidence: 68%
“…This was consistent with some previous reports that non-geminate triplets did not play an important role in the fission/fusion dynamics in amorphous organic solids [16,19]. This differs considerably from previous observation of triplet dynamics in rubrene crystals [24][25][26], where triplet excitons can freely diffuse in crystal and collide with each other to form intermediate 1 (TT) i states. In that case, the intensity of delayed fluorescence is proportional to n(t) 2 , where n(t) is triplet exciton density.…”
Section: Resultssupporting
confidence: 68%
“…This value is determined only by the observed decay dynamics and measured pulse fluences, and it agrees well with previous estimates. 2,3 Put another way, the measurements in Fig. 3 imply that quadratic recombination leads to the destruction of 50% of the original excitation after $3 ns at an average excitation density at the surface of the crystal corresponding to q 0 $ 0.5 Â 10 20 .…”
Section: à3mentioning
confidence: 99%
“…2,3 Singlet fission in rubrene single crystals has not been consistently described yet. Tao et al 4 have observed a $100 ps fast decay of a photoinduced infrared absorption band which they assigned to singlet excitons, but they interpreted the decay as caused by exciton dissociation, not fission.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, rubrene shows high singlet fission efficiencies in both, single crystals 22,23 and amorphous thin films 24 . Rubrene became thus a model system to study intermolecular interactions and charge transport properties of molecular solid states 10,20,21,[25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%